Technostress in Airport Ground Handling: The Mediating Role of Psychological Resilience in the Effect of Mindfulness (Third Sector Social Economic Review, 2026)
This study examines the relationship between mindfulness (MF) and technostress (TS) among airport ground handling employees and tests the mediating role of psychological resilience (PR) in this relationship. Using a quantitative research design, survey data were collected from ground handling personnel (N=384). Mindfulness was measured with the Mindful Attention Awareness Scale developed by Brown and Ryan (2003) and adapted into Turkish by Özyeşil (2011); psychological resilience was assessed using Işık’s (2016) scale; and technostress was measured with the scale developed by Tarafdar et al. (2007) and adapted by Türen et al. (2015). Construct validity was confirmed through exploratory and confirmatory factor analyses. Hypotheses were tested via Pearson correlation analysis and a bootstrap-based mediation approach (PROCESS Model 4; 5,000 resamples; 95% confidence intervals). The findings indicate that mindfulness positively predicts psychological resilience, psychological resilience negatively predicts technostress, and the effect of mindfulness on technostress also operates indirectly through psychological resilience. The indirect effect was significant, as its confidence interval did not include zero, supporting partial mediation. Overall, the results highlight the importance of strengthening psychological resources in managing technostress in airport ground handling operations.
Keywords: Mindfulness; psychological resilience; technostress; airport; ground handling